Human splenic macrophages as a model forin vitroinfection with Mycobacterium tuberculosis (2023)
Macrophages play an important role during Mycobacterium tuberculosis (MTB) infection. In humans most of the studies on MTB-macrophage interactions have been performed using circulating monocytes and monocyte-derived macrophages. However, little research has been performed on this interaction using tissue macrophages. Herein, we used human splenic macrophages to characterize particular responses to MTB infection. Based on morphological, biochemical, and immunological markers, splenic adherent cells exhibit characteristics of tissue macrophages. They were able to efficiently phagocytose both live and heat-killed (h-k) MTB H37Rv. Upon infection with live, but not h-k MTB, an increase in secreted TNF-alpha was elicited. Splenic macrophages produced high basal levels of IL-10; however, infection with live or h-k MTB resulted in decrease IL-10 secretion. Both IL-12p40 and IL-12p70 basal levels were also decreased upon infection with live or h-k MTB; however, while the reduction for IL-12p40 levels was observed at earlier time points (4h) for both live and h-k MTB, infection with live MTB, but not h-k MTB, resulted in a time-dependent secretion of IL-12p40 at 24 and 48h after infection. IL-12p70 levels were completely reduced upon infection by either live or h-k MTB. These results support that human splenic macrophages may represent a potential useful model to study MTB-macrophage interactions in vitro.